Education and science: current trends - Razumov A. A., Ermakov D. N., Surkova G. V., Shpak A. S., Ivanov A. A., Sizykh D. S., Sizykh N. V., Prisiazhnaia I. M., Prisiazhnaia S. P., Granitsa I. V., Bakhmisova M. A., Sakmarova L. A., Batanov M. S., Barankin S. I., Strelkov V. I., Chibilyova V. P., Chibiliov A. A., Leventsov V. A., Leventsov A. N., Ruban F. M., Alisin V. V., Malinin V. B., Salivanov A. V., Trapaidze K. Z., Chernopiatov A. M., Bondareva E. I., Pankova N. A., Ivanova N. G., Shchebliakov E. S., Zhuravleva O. N., Sarvanova Z. A., Dorofeev S. N., Novikova T. S. (Education and science: current trends, 2018)
modern domestic culture is in search of a new psychological paradigm that would meet the specifics of the Russian mentality. This paradigm reveals itself in the special organization of information, which is reduced to a compact form of the matrix, which essentially optimizes its composition. The reliance on the matrix approach allows us to introduce a second information regulation loop, overcoming the weaknesses of the Russian mentality.
Keywords: парадигма; понятие; инновация; innovation; матрица; paradigm; concept; matrix